The influence of customer experience and destination image on interest to return visit - Indra Kurniawan; Ferdi Setyawan (Enrichment : Journal of Management, 2023)
This study aims to examine the effect of customer experience and destination image on the intention to return to Kedai Tanah Senja Wonosalam. The explanatory research method is used by collecting data in the field. The research population consisted of all customers of the Tanah Senja Wonosalam Tavern, with a sample of 100 customers. Data analysis was performed using multiple linear regression statistical methods, as well as testing the hypothesis and the coefficient of determination. Based on the results of the study, it was found that there was a significant influence between customer experience and intention to revisit Kedai Tanah Senja. That is, the higher the customer experience, the higher the customer's intention to revisit. In addition, a significant influence was also found between destination image and intention to revisit Kedai Tanah Senja. A high destination image has the potential to influence customers to make repeat visits. Thus, this study concludes that customer experience and destination image play an important role in increasing intention to return to Kedai Tanah Senja Wonosalam.